THE HUMAN RIGHTS ENFORCEMENT AS AN IDENTITY OF THE AMERICAN QUAKERS IN THE ERAS BEFORE TWENTIETH CENTURY - Nuriadi . (Humaniora, 2014)
This paper discusses how and why the Quakers dealt with human rights issues in the United States before 20th century, ranging from the mid 17th century to the mid 19th century. It applies Nash Smith’s interdisciplinary theory as a theoretical approach. The Quakers, as a Christian religious group, had got several features or identities since George Fox declared its existence in England in the mid of 17th century. They lived in simplicity, adopted the principle of pacifism, rejected paying tith and tax, rejected taking off hat, used archaic words, and so forth. However, the Quakers in the United States had shown a new feature or identity; namely, the enforcement of human rights in the eras before the 20th century. The human rights enforcement was motivated by their piety and loyality to the Quakerism. In other words, it was an expression of their belief in Quakerism. This theology empowered their thoughts and actions in responding issues pertaining to human rights of the minorities i.e. the Indians or Native Americans, the African-Americans, and women along the span of time. Their goal was to let the minorities enjoy their unalienable rights as what most of white men had enjoyed.